Nurturing Care Practices and Developmental Outcomes in Acutely Ill Children Aged 12-36 Months: A Cross-Sectional Study - Amalina Batrisyia Agustin; Fitri Haryanti; Ika Parmawati; Akhmadi Akhmadi (Poltekkes Kemenkes Surakarta, 2025)
Background: The period from 12 to 36 months represents a critical window for child development, yet the relationship between nurturing care practices and developmental outcomes during acute illness remains poorly understood. This study aimed to determine the relationship between maternal nurturing care practices and the developmental status of acutely ill children aged 12-36 months in Bantul Regency, Yogyakarta, Indonesia. Methods: A cross-sectional descriptive-analytic study was conducted among 70 mother-child pairs recruited through consecutive sampling. Maternal nurturing care practices were assessed using a modified questionnaire adapted from UNICEF Knowledge, Attitudes, and Practices tools. Child development was evaluated using the Indonesian Pre-Screening Development Questionnaire (KPSP). Maternal depression was measured using the Beck Depression Inventory-II. Data were analyzed using Fisher's exact test, with statistical significance set at p<0.05. Results: The majority of mothers (57.1%) demonstrated poor nurturing care practices, while 84.3% of acutely ill children showed age-appropriate development. Most mothers (80.0%) were aged 20-35 years, had secondary education (50.0%), and were not experiencing depression (68.6%). Fever was the most common acute illness (44.3%), with a median duration of 3 days. No statistically significant association was found between maternal nurturing care practices and child development status (p=0.331, OR=2.250, 95% CI: 0.543-9.330). Additionally, established developmental predictors including maternal education (p=0.745), family economic status (p=1.000), and maternal depression (p=0.873) showed no significant associations with developmental outcomes. Conclusion: These findings highlight the need for context-specific nurturing care assessment tools and longitudinal research designs to better understand the complex dynamics between caregiving practices, acute illness, and developmental outcomes in young children.